The status of East Asian free trade agreements - Yunling Zhang; Minghui Shen (Asian Development Bank Institute (ADBI), 2011)
Free trade agreements (FTAs) have become a prominent feature of the multilateral trading system and an important instrument of trade policy for members of the World Trade Organization (WTO). The proliferation of FTAs is the result of a number of factors, from the economic to the political. East Asia is with no exception involved in the process and witnessing the establishment of multilayered FTAs. Pioneered by the Association of Southeast Asian Nations (ASEAN) in 1992 when it initiated the ASEAN FTA (AFTA), and encouraged by ASEAN+1 (ASEAN plus one country) FTAs, more and more economies in east Asia are involved in FTAs, although the characteristics of these FTAs differ according to their background and circumstances. When the proliferation of FTAs in east Asia benefits the regional trade and economic growth, questions have been raised about Asian noodle bow effect, pointing out multi-layered FTAs in east Asia have created new trade barriers and raised the cost of business in the region. To this end, east Asia needs to progress from the proliferation of multilayered FTAs to a region-wide FTA with wider participation and broader coverage.
Keywords: F10; F13; F15; 330; Freihandelszone; Handelsabkommen; Wirtschaftswachstum; Außenhandelsliberalisierung; Ostasien